Modeling and Simulation of a PV generator and Maximum Power Point Tracking Controller Using Simscape - Singh, Rajinder (My University, 2015)
The most common way of harvesting the solar energy through photovoltaic panels or array is very popular and effective to receive photon energy from the sun. This energy intern, converted to electrical energy. In the present work the modeling and simulation of a PV generator considering practical on-site condition is performed. Its characteristics at different irradiation and temperature levels have been obtained by using the MATLAB/Simulink software. In the process of simulation, the constant and variable load condition are implemented. After simulation of the PV generator, its Maximum Power point is obtained with the help of two different techniques. The two different techniques are namely Perturbation and Observation method and fuzzy logic control (FLC) method which are mostly used to track the Maximum Power Point (MPP) of a PV generator by the variation of temperature and insolation. The main advantages of these two methods are to increase the efficiency of the PV generator and to extract the maximum power from the panel in least time. A DC-to-DC converter model is designed using MATLAB/Simulink in order to determine the performance of the MPPT controller. The output of both the MPPT controller remains connected with the Ideal switch of the converter to extract the maximum power output of the PV generator. The simulation results based on MATLAB-Simscape Systems are explained and shown.
ME, EIED
Keywords: PV Array; MPPT; Fuzzy Logic Controller (FLC); DC-DC Converter; EIED